Standardization of Nursery Media and Sowing time for Germination of Sandalwood (Santalum album L.) Seed. - Mohapatra, S. R.; Bhol, N.; Nayak, R. K. (Indian Forester, 2019)
The investigation on standardization of nursery media and sowing time for germination of Sandalwood (Santalum album L.) seed was carried out at College of Forestry, Orissa University of Agriculture and Technology (O.U.A.T), Bhubaneswar, India during 2014 2015 with the objective to improve the quality of planting material in short period. This investigation was necessary because Sandalwood is the second most expensive wood in the world, next to the African Blackwood (Dalbergia melanoxylon). Its seeds need suitable nursery media and proper time of sowing for better germination and growth. This experiment was conducted in nursery under split plot design. Two types of seeds like seeds with seed coat and seeds without seed coat were taken. Freshly collected sandalwood seeds were treated with 0.05% Gibberellic acid and sown in the month of April, May and June in 8 different combinations of germination media such as T1 (sand), T2 (sand: perlite in 1:1), T3 (perlite), T4 (sand: red soil in 1:1), T5 (perlite: red soil in 1:1), T6 (sand: red soil: FYM in 1:1:1), T7 (sand: perlite: red soil) and T8 (red soil). Seeds sown without seed coat in the month of 8 May in sand (S2T2M1) recorded significantly maximum germination percentage (55%), germination capacity (70%) and germination energy (41.50%). Similarly, seeds without seed coat sown in May in the mixture of sand and perlite in 1:1 ratio (S2T2M2) performed at par with (S2T2M1). However, seeds with seed coat sown in April in red soil (S1T1M8) performed poor for all parameters under study.